Kalimat Imperatif (Amr) dalam Al-Qur’an: Perspektif Balagah dan Implikasinya dalam Penafsiran - Muhammad Ardiansyah; Mohamad Harjum; Dudung Abdullah (Dirosah Islamiyah, 2026)
This study examines imperative sentences (amr) in the Qur’an with a focus on their forms, meanings, and the role of context in interpretation. This topic is important because imperative expressions in the Qur’an do not always indicate obligatory commands, but may convey various meanings depending on the context in which they appear. The study aims to analyze the forms of amr in the Qur’an, identify their functions and meanings from the perspective of balāgah, and explain the role of context in determining the meaning of imperative expressions. This research employs a qualitative-descriptive library research method. The data were collected from Qur’anic verses, classical books of balāgah, tafsir literature, uṣūl fiqh references, and relevant scholarly articles. The analysis uses the balāgah approach, particularly the science of ma‘ānī, by considering siyāq al-kalām and contextual indicators (qarīnah) accompanying the verses. The findings reveal that amr in the Qur’an appears in several forms, including fi‘il amr, fi‘il mudhāri‘ accompanied by lām al-amr, isim fi‘il amr, masdar functioning as fi‘il amr, and expressions containing imperative meanings. Furthermore, amr carries various semantic functions such as ibāḥah, takhyīr, tahdīd, ta‘jīz, du‘ā, iltimās, naṣīḥah, ikrām, imtinān, taḥqīr, and takwīn. This study concludes that context plays a crucial role in determining the meaning of imperative expressions in Qur’anic interpretation and contributes to a deeper understanding of Qur’anic rhetoric and interpretation